The interaction effect between information management and innovation model on performance of innovative start-ups in Thailand / Rattanawadee Sonthiprasat and Julsuchada Sirisom - Sonthiprasat, Rattanawadee (Faculty of Computer and Mathematical Sciences, 2012)
The purpose of this study is to evaluate the relationship between various levels of information technology management and effective business innovation for the startups in Thailand. The new implication gains from the advantages of information technology management adoption and knowledge sharing that would improve the process of decision making for startups to consider the adoption of information technology management and its open innovation management. The data collection came from the online survey. It was subjected to analyzing by statistical tools. Data was analyzed from research questions which included the descriptive statistics, structural equation modeling, analysis of variance (ANOVA), chi-square test, and multiple regression analysis. The reliability and factor analyses were also added. The results showed that 70.9% of the variation in the firm’s performance could be explained by IT management. The variation in the balanced scorecard of the startups could be significantly affected by open innovation. The results from the mediator effect were accepted. Additionally, the mediated effects of open innovation between IT management and firm performance was established.